Cognitive, Socioemotional and Behavioral Returns to College Quality - Utteeyo Dasgupta; Subha Mani; Smriti Sharma; Saurabh Singhal (Institute of Labor Economics (IZA), 2017)
We exploit the variation in the admissions cutoffs across colleges of a leading Indian university in a regression discontinuity framework to estimate the causal effects of enrolling in a selective college on: cognitive attainment, behavioral preferences, and Big Five personality. We find that enrolling in a selective college improves only females' exam scores. Further, marginally admitted females in selective colleges become less overconfident and less risk averse while males in selective colleges experience a decline in extraversion and conscientiousness. Higher attendance rates among females explain the gender differences in returns to better college and peer environment.
Keywords: I23; C9; C14; J24; O15; 330; cognitive attainment; behavior; personality; college quality; peer effects; India